A Direct One‐Pot Synthesis of Asymmetric Dehydrobenzopyrido[12]annulenes and Their Physicochemical Properties. Issue 31 (23rd August 2017) - Baxter, Paul N. W.; Karmazin, Lydia; DeCian, André; Varnek, Alexandre; Gisselbrecht, Jean‐Paul; Strub, Jean‐Marc; Cianferani, Sarah
Abstract : A direct one‐pot synthesis of asymmetric dehydrobenzopyrido[12]annulenes2 and3 containing one or two pyridine rings is reported that employs a Stephens–Castro mediated cross‐coupling of mixtures of ethynylcuprate precursors. The spectroscopic and theoretical properties of2 and3 are compared to those of the threefold symmetric dehydrotribenzo[12]annulene1, and dehydrotripyrido[12]annulenes4 and5 and dehydrodibenzodipyrido[16]annulene byproduct6, and showed1 –5 to be essentially isoelectronic band gap materials whose electron accepting ability increases with increasing nitrogen incorporation. The structures of2, 4 and6 were also unambiguously characterized by X‐ray crystallography. The results highlight the potential dehydroaryl[12]annulenes incorporating pyridines offer for the construction of high carbon content electronic materials. Abstract : Asymmetric dehydroaryl[12]annulenes2 and3 were directly prepared by a one‐pot Stephens–Castro mixed‐coupling from cuprates8 and10 . Physical and theoretical studies showed1 –4 to have isoelectronic band gaps with electron accepting ability increasing with increasing nitrogen content.